Peran Masjid sebagai Lembaga Kaderisasi Umat di Tengah Dinamika Sosial : Sebuah Tinjauan Historis dan Kontemporer - Rafifah Qanita; Nursyafna Nursyafna; Muhammad Fadhly; Wismanto Wismanto (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This research discusses the role of mosques as Islamic cadre formation institutions in facing modern social dynamics. Through a historical approach, this article explores the function of mosques since the beginning of Islam, when mosques became centers for community development that included religious education, character cultivation, and leadership development. In a contemporary context, this research examines the adaptation of mosques to the challenges of globalization, social change and technological developments. The aim of this research is to analyze and describe the strategic role of mosques as Islamic cadre formation institutions in the context of social dynamics, both from a historical and contemporary perspective. This research uses a qualitative method with a literature study approach, regarding journals and books regarding historical and contemporary reviews of the role of mosques, especially in character development, education and leadership. The research results show that mosques not only function as places of worship, but also as effective agents of social change, contributing to the formation of character and solidarity among the people. Efforts to revitalize the function of mosques through technology integration, collaboration with educational institutions, and community-based cadre programs show the potential of mosques in developing people who are ready to face the challenges of the times.